Modulating Fundamental Resonance in Capacitive Coupled Asymmetric Terahertz Metamaterials. Issue 1 (December 2018) - Rao, S.; Srivastava, Yogesh; Kumar, Gagan; Roy Chowdhury, Dibakar
Abstract In this work, we experimentally investigate near-field capacitive coupling between a pair of single-gap split ring resonators (SRRs) in a terahertz metamaterial. The unit cell of our design comprises of two coupled SRRs with the split gaps facing each other. The coupling between two SRRs is examined by changing the gap of one resonator with respect to the other for several inter resonator separations. When split gap size of one resonator is increased for a fixed inter-resonator distance, we observe a split in the fundamental resonance mode. This split ultimately results in the excitation of narrow band low frequency resonance mode along with a higher frequency mode which gets blue shifted when the split gap increases. We attribute resonance split to the excitation of symmetric and asymmetric modes due to strong capacitive or electric interaction between the near-field coupled resonators, however blue shift of the higher frequency mode occurs mainly due to the reduced capacitance. The ability of near-field capacitive coupled terahertz metamaterials to excite split resonances could be significant in the construction of modulator and sensing devices beside other potential applications for terahertz domain.